Radical sanation of laicized priest when spouse refuses to renew consent Canon 1161 - Kaslyn, Robert J. 1956- (2006)
Mike, a priest for some fifteen years, decided in 1978 to leave the active priestly ministry and did so without completing any paperwork. Within a few months he entered into a civil union with Jane, a Catholic free to marry. In 1988, Mike requested and received a dispensation from his priestly obligations, including celibacy, allowing him to return to the lay state and to enter into marriage. Despite ten years of discussion with his wife, Jane as yet refuses to renew consent according to canonical form. She claims that her consent before the justice of the peace in 1978 was true consent for her and there is no need to renew that consent or to make new consent. Except for this issue, Mike and Jane have a good relationship and intend to remain married. Nonetheless, Mike is very concerned about the spiritual dimensions concerning regularizing his civil marriage to Jane in the eyes of the Church and wishes to learn which options are available for him.
Keywords: Katholische Kirche; Eherecht; Sanatio in radice; Konsenserneuerung